2008
DOI: 10.1038/emboj.2008.20
|View full text |Cite
|
Sign up to set email alerts
|

Role of 16S ribosomal RNA methylations in translation initiation in Escherichia coli

Abstract: Translation initiation from the ribosomal P‐site is the specialty of the initiator tRNAs (tRNAfMet). Presence of the three consecutive G‐C base pairs (G29‐C41, G30‐C40 and G31‐C39) in their anticodon stems, a highly conserved feature of the initiator tRNAs across the three kingdoms of life, has been implicated in their preferential binding to the P‐site. How this feature is exploited by ribosomes has remained unclear. Using a genetic screen, we have isolated an Escherichia coli strain, carrying a G122D mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 45 publications
3
91
1
Order By: Relevance
“…Earlier studies in yeast showed that although overproduction of initiator tRNA could sustain a strain lacking all five elongator tRNA Met genes, a strain lacking all its chromosomal copies of the initiator tRNA Met genes could neither be sustained by overproduction of the elongator tRNA Met nor by overproduction of initiator tRNA Met lacking the 3G-C pairs (18). The only known exceptions to the presence of the 3G-C pairs are some species of Mycoplasma (which has the smallest bacterial genomes and is most often parasitic) (11) and Rhizobium (which lives in symbiotic association).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies in yeast showed that although overproduction of initiator tRNA could sustain a strain lacking all five elongator tRNA Met genes, a strain lacking all its chromosomal copies of the initiator tRNA Met genes could neither be sustained by overproduction of the elongator tRNA Met nor by overproduction of initiator tRNA Met lacking the 3G-C pairs (18). The only known exceptions to the presence of the 3G-C pairs are some species of Mycoplasma (which has the smallest bacterial genomes and is most often parasitic) (11) and Rhizobium (which lives in symbiotic association).…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the belief that the intact 3G-C pairs of initiator tRNA are an essential feature of living systems. The only known exceptions are in some species of Mycoplasma and Rhizobium, where the single initiator tRNA gene produces tRNAs having the first and/or last G-C pair represented by A-U and G-U, respectively (11). Understanding how initiation occurs in these species has therefore been a major puzzle in the field of translation.…”
mentioning
confidence: 99%
“…Furthermore, m 6 2 A1518 and m 6 2 A1519 impact initiation 67 possibly via m 3 U1498 whose backbone interacts with m 6 2 A1519, while its modified base contacts the mRNA backbone. The methyl groups of m 3 U1498 and m 4 Cm1402 form part of the binding site for the initiation codon and modulate translation initiation 13,14 by steric encumbrance and/or by preventing direct hydrogen bonds with the mRNA backbone. b, Constitutive rRNA modifications in the E. coli 70S ribosome (list adapted from ref.…”
Section: Extended Datamentioning
confidence: 99%
“…Clusters of several rRNA modifications are essential for ribosome function, whereas individual rRNA modifications have an important role in fine-tuning the active centres of the ribosome, as well as in antibiotic resistance and sensitivity 11 . Six individual rRNA modifications at the decoding centre modulate the efficiency and accuracy of translation initiation by stabilizing interactions in the P site [12][13][14] . The present structure shows that the methyl group of m 2 G966 in 16S rRNA may act as a 'backstop' for the initiator tRNA, thereby stabilizing base-pairing with the initiation codon ( Fig.…”
mentioning
confidence: 99%
“…49 Methionine is important for quorumsensing. 48,51-52 The intracellular concentrations of methionine and N 10 -formyl THF (products of one-carbon metabolism), shown to be important in protein synthesis, 53 might have acted as the indicators for energy status of the cell or the richness of the surrounding environment in the prebiotic soup. Evolutionary importance of changes in the tRNA gene and energy efficiency with bacterial growth has already been well characterized.…”
Section: Discussionmentioning
confidence: 99%